2017
DOI: 10.1136/vr.103859
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for road traffic accidents in cats up to age 12 months that were registered between 2010 and 2013 with the UK pet cat cohort (‘Bristol Cats’)

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms AbstractRoad traffic accidents (RTAs) are a common cause of death and injury in domestic cats, and a concern to many owners. This study assessed potential risk factors for RTAs in cats up to 12 months of age within a UK cat cohort known as 'The Bristol Cats Study'. Data were obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 16 publications
3
32
0
1
Order By: Relevance
“…Previous studies have suggested that male cats are at higher risk of trauma events compared with female cats (Rochlitz , , Egenvall et al ). However, the current study did not identify strong evidence for an association between sex and the risk of mortality due to trauma‐related injuries, a result consistent with a study on cats less than 12 months old (Wilson et al ). Although the descriptive statistics suggested that a lower proportion of females than males died from trauma compared with deaths from non‐trauma disorders, this difference was not statistically significant when tested in the GLM framework which takes into account multiple variables.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Previous studies have suggested that male cats are at higher risk of trauma events compared with female cats (Rochlitz , , Egenvall et al ). However, the current study did not identify strong evidence for an association between sex and the risk of mortality due to trauma‐related injuries, a result consistent with a study on cats less than 12 months old (Wilson et al ). Although the descriptive statistics suggested that a lower proportion of females than males died from trauma compared with deaths from non‐trauma disorders, this difference was not statistically significant when tested in the GLM framework which takes into account multiple variables.…”
Section: Discussionsupporting
confidence: 85%
“…Traumatic events, defined as tissue damage caused by an unexpected external force (Menon et al ), are a significant cause of injury and death in domestic cats in the UK (O'Neill et al , , Wilson et al ) and worldwide (Egenvall et al ). Trauma was the most common cause of mortality (12·2%; O'Neill et al ) in cats attending veterinary clinics in England, and accounted for almost half of all mortality cases in cats younger than three years (O'Neill et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Outdoor and indoor lifestyles each carry risks for cats and the right decision is the one where the benefits outweigh the risks in each particular case. When assessing how to help clients make this decision, research can be useful, such as the data from Wilson and others (2017) and Rochlitz (2003a, b), which found that reflective collar wearers formed a greater proportion of RTA victims, (although this plausibly represented recognition of risk by owners). Wilson and others' paper is a significant step towards helping veterinary surgeons and the rest of the veterinary team in advising on preventive welfare issues.…”
Section: The Indoor Environmentmentioning
confidence: 99%
“…IT is encouraging to see the question being raised by Yeates and Yates (2017) concerning the welfare of cats being kept indoors or allowed to roam free, against the background of road kill data provided in the ‘Bristol Cats’ study by Wilson and others (2017). They face the culturally accepted norm of cats being allowed to leave their owners' properties, a common situation with the dog population until the Road Traffic Act 1988 and the Control of Dogs Order 1992.…”
mentioning
confidence: 99%
“…The ‘Bristol Cats’ study of young cats being killed or injured in road traffic accidents drew the obvious conclusion that cats would be safer if they were never allowed to roam free and hunt along roadsides, especially roads with fast vehicular traffic (Wilson and others 2017). However, the authors assert that ‘there are a number of health and welfare concerns associated with exclusively indoor cats’.…”
mentioning
confidence: 99%